PENGARUH HASIL PEMERIKSAAN BPK TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Endri Parwanto; Puji Harto (Diponegoro Journal of Accounting, 2017)
This study aimed to analyze the effect of the audit results by BPK on the financial performance of local government in Jawa Tengah Province. The variables in this study are audit opinion, audit findings, the follow up of audit results, and timeliness in reporting financial statements. The financial performance measures are using effectiveness ratio and efficiency ratio. This study uses secondary data from audit report by Badan Pemeriksa Keuangan Republik Indonesia and financial statements of local government in Jawa Tengah Province in 2013 and 2014. The data and hypothesis are tested by using partial least square (PLS) method. The results showed that not all of the audit results by BPK have a significant effect on financial performance of local government. Audit opinion and timeliness in reporting financial statement have a significant effect on financial performance of local government, meanwhile audit findings and the follow up of audit results have no significant effect on financial performance of local government.